The Art of Unarmed Stage Combat - Najarian, Robert (Routledge, 2015)
The Art of Unarmed Stage Combat is a guide to the principles and techniques of theatrical violence, combining detailed discussions of the mechanics of stage fighting with the nuances of acting decisions to make fighting styles reflect character and story. Expert Fight Director Robert Najarian offers never-before-published games and exercises that allows actors to develop the skills and concepts for performing violence for stage and screen. This title utilizes a unique system of training techniques that result in stage violence that is both physically engaging for the performer, while remaining viscerally engaging for the audience. This book is written for the actor and fight director.